APPLYING TRANSCRIPT 1.23 IN IMPROVING THE STUDENTS’ WEAK PRONUNCIATION AND CONNECTED SPEECH - Azman, .; ., Sudarsono; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This true experimental research is mainly aimed at investigating the effectiveness of using Computer-assisted Pronunciation Teaching (CAPT) application software Transcript 1.23 in teaching English pronunciation of weak forms and connected speech. The data used to measure the effectiveness of the application of CAPT software in the treatment is collected from participants’ oral performance in the form of voice records. The pre-test and pos-test data from the participants is analysed and compared to measure the effect of the given treatment. The result of the research shows a strong effect of the application of the software to improve the quality of the participants’ pronunciation of weak forms and connected speech. The effectiveness of the software application in the treatment is categorised as strong according to the criteria developed by Cohen. Key Words: Effectiveness, CAPT, Transcript 1.23, Weak Pronunciation, Connected Speech Abstrak: Penelitian true experimental ini terutama bertujuan untuk meneliti efektifitas penggunaan aplikasi pengajaran lafal dengan bantuan aplikasi perangkat lunak komputer Transcript 1.23 pada pengajaran lafal bentuk lemah dan lafal bersambung. Data yang digunakan untuk mengukur efektifitas penggunaan perangkat lunak pengajaran lafal dengan bantuan komputer tersebut dalam pengajaran lafal adalah berupa penampilan lisan partisipan dalam bentuk rekaman suara. Data sebelum dan setelah perlakuan diberikan dianalisis dan dibandingkan guna mengukur pengaruh perlakuan yang diberikan. Hasil penelitian menunjukkan pengaruh yang kuat dari penggunaan perangkat lunak tersebut untuk meningkatkan kualitas lafal lemah dan lafal bersambung oleh partisipan. Keefektifan penggunaan perangkat lunak tersebut dalam pengajaran dikategorikan kuat menurut kriteria yang dibuat oleh Cohen. Kata Kunci: Keefektifan, CAPT, Transcript1.23, Lafal lemah, Ujaran bersambung